As contribuições da abordagem pikleriana para uma prática inclusiva no berçário - Abreu, Gabriela Vieira Soares de (2021)
This descriptive-exploratory and qualitative study aimed to investigate how the singularities in the development and learning of babies are welcomed in a nursery inspired by the Piklerian approach. More specifically, the study aimed to 1) understand the educators' conceptions of the babies' development and learning processes; 2) analyze how individualized and respectful care with babies contributes to the fulfillment of their individual development and learning needs; 3) analyze how free motor skills and the possibility of autonomous experiences contribute to the fulfillment of babies' individual development and learning needs; and 4) investigate how the principles of the Piklerian approach are aligned with the principles of Inclusive Education. To this end, the study was developed within a private school of Early Childhood Education located in the municipality of Porto Alegre, which has been inspired by the Piklerian approach. Three babies and their respective reference educators participated as research subjects. For data collection, the study used the Focus Group as the general methodological strategy for conducting meetings with the educators, via Zoom Platform. In addition, videos and photos of the babies were recorded using the Narrative Descriptions methodology and taken as the corpus of analysis along with the transcripts of the meetings. The material was analyzed using the methodology of Textual Discourse Analysis. The results found support the initial hypothesis that the piklerian approach provides subsidies for an inclusive practice in the nursery, given that it emerged in the primary intention of welcoming the differences of babies away from their relatives, in the search to eliminate or mitigate any psychic risks in its development. Although the Piklerian approach was developed in a specific post-war context in Hungary, involving cultural aspects of that place, its basic principles of respect for the baby are universal, serving as the basis for an inclusive practice in different countries, as well as in Brazil. Keywords: Early Childhood Education; Inclusive Education; Piklerian approach; singularities; nursery.